Jalan Masuk Kota Majapahit: Kajian Situs-Situs Arkeologi di Kecamatan Sumobito, Jombang, Jawa Timur - Nurhadi Rangkuti (Berkala Arkeologi, 2005)
The remnants of past community activities on the banks of the Brantas tributary in the Sumobito District have raised problems regarding the site's function. Are the sites located on the riverbank a river port site as the entrance to the Majapahit city area in the Trowulan area? This paper aims to determine the function of the site and answer the problem of access to the city of Majapahit in Trowulan, Mojokerto, especially from the northwest.